How are Organic Farming Inputs Evaluated? - James J. Ferguson (EDIS)
The purpose of this document is not to list organic farming inputs but to explain how these materials are evaluated and where to find current online lists of inputs and regulations. This document is HS966, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 2004.